Perceived severity and susceptibility towards leptospirosis infection in Malaysia - Sukeri, Surianti; Wan Mohammad, Wan Mohd Zahiruddin; Shafei, Mohd Nazri; Awang Hamat, Rukman; Osman, Malina; Tengku Jamaluddin, Tengku Zetty Maztura; Daud, Aziah (Multidisciplinary Digital Publishing Institute, 2020)
Background: Perceived severity and susceptibility refers to one's belief of the seriousness and the risk of contracting a specific disease. It is an essential study in public health as it assists in the understanding of the motivating factors towards disease prevention. This qualitative study aimed to explore perceived severity and susceptibility towards leptospirosis infection among respondents in two states of Malaysia. Methods: Focus group discussions using the phenomenology approach was conducted involving 72 respondents in Selangor and Kelantan. Data were examined using content analysis. Results: Respondents perceived leptospirosis infection as severe due to its poor disease prognosis and complications. However, some rated it less severe when compared with other chronic diseases such as cancer and AIDS. Their perceptions were influenced by their knowledge about the disease, media portrayal and frequency of health campaigns by the government. All respondents believed they were not susceptible to the disease. Conclusion: The low perceived susceptibility of leptospirosis infection is a matter of concern as it may contribute to respondents' lack of motivation towards preventing the disease. The study findings may provide the basis for health promotional activities designed to heighten public perceived threat towards leptospirosis infection and thereby improving preventive health behaviors for avoiding leptospirosis.